Pengembangan Aplikasi Closing Register Berbasis Web untuk Membantu Customer Service Digital Marketing - Titan Parama Yoga Titan; R. Yadi Rakhman Alamsyah; Venia Restreva Danestiara; Aliman Fauzi (Ma'soem University, 2023)
This research was conducted to solve sales data collection problems in the digital marketing business at CV. Icommits Work Solutions. The problem that occurs is that the process of entering data is inefficient and still uses ineffective conventional methods. By doing this research the authors are looking for a way to solve this problem, and the way to solve it is to develop the Closing Register application. The purpose of developing the Closing Register application is to simplify the process of entering data and monitoring sales data so that consumers, customer service and CS admins do not need to expend a lot of energy in the sales data collection process. The Closing Register application is made with the RAD (Rapid Application Development) design model, as well as the technology used in application development, namely ReactJS as a framework in charge of creating web admin views, Flutter as a framework in charge of creating mobile displays, MySQL as a database, and ExpressJS as a framework whose job is to create an API (Application Programming Interface). The results showed that technologies are used to create up-to-date applications and for long-term use, so that later these applications can be used directly and are useful for digital marketing businesses.